(untitled) (Collection of scientific works «Scientific Problems of Architecture and Urban Planning» | ODABA, 2026)
This article examines the trajectories of post-socialist transformation in Eisenhüttenstadt between 1990 and 2025 as a planned monocity originally developed around a cityforming enterprise – Steelworks Combine East (Eisenhüttenkombinat Ost). The study analyzes how spatial, institutional, and socio-cultural changes intersect under conditions of deindustrialization, demographic decline, and state-led programs of «managed shrinkage». These processes resulted in large-scale demolition of residential buildings, selective concentration of resources in preserved urban cores, and substantial reconfiguration of infrastructural and service systems. Drawing on a combination of critical literature review, analysis of planning documents, open-access statistical data, and fieldwork, the article conceptualizes Eisenhüttenstadt’s post-socialist development as a multi-layered and actor-driven transformation rather than a linear decline. Particular attention is paid to the role of institutional actors at different governance levels, as well as to locally embedded cultural agents and initiatives that have actively contributed to the reinterpretation of socialist urban heritage. The findings demonstrate that post-socialist trajectories in monotowns are shaped by the interaction of strategic instruments – such as privatization regimes, urban restructuring programs, and heritage protection frameworks – and tactical practices, including cultural interventions, adaptive reuse, and network-based local mobilization. Eisenhüttenstadt is discussed as a transformation shaped by deliberate actions of multi-level actors, including state-led restructuring instruments, municipal planning and housing management, and local cultural initiatives. The case illustrates how strategic programs and tactical practices interacted in housing demolition, resource re-concentration, and heritage re-interpretation. Methodologically, the paper reconstructs key phases through analysis, offering a comparative lens for post-socialist monotowns, including Ukraine.